ANALISIS BIAYA DAN PENDAPATAN USAHATANI JAGUNG HIBRIDA DI DESA CIHAUR KECAMATAN MAJA KABUPATEN MAJALENGKA - Vina Rachmadina; Zumi Saidah; Lucyana Trimo; Eliana Wulandari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Corn is a food crop with high economic value considering its position as the main source of carbohydrates and protein substitute rice also be used as raw material for animal feed which has a fairly dominant composition. Majalengka Regency is one of the districts in West Java Province which has a position as a corn producing area with a total production of 151,646 tons in 2017. The purpose of this study is to determine: (1) The amount of production costs in hybrid corn farming per one planting season, (2) The amount of hybrid corn farming income and revenue per one planting season. This research is a quantitative research with descriptive analysis which conducted in Cihaur Village, Maja District, Majalengka Regency. The sampling technique used was simple random sampling of 180 population members and 64 respondents were taken. The results showed that: 1) The amount of production costs in hybrid corn farming is Rp3.686.567,97 per 0,77 ha per one planting season, 2) The amount of income in hybrid corn farming is Rp6.070.791,41 per 0,77 ha per one planting season and  revenue in corn farming is Rp9.757.359,38 per 0,77 ha per one planting season. Based on R/C and B/C Ratio analysis, hybrid corn farming in Cihaur Village  Maja District  Majalengka Regency is feasible and profitable to cultivate.